Pengaruh Keadilan Organisasional terhadap Employee Engagement Dimoderasi Etika Kerja Islam - Novia Hariani; Muafi Muafi (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2021)
Justice is an important factor in improving employee performance. In its application, companies must apply good business ethics so that the relationship between justice and performance can increase. Several previous studies have discussed the relationship between fairness and performance, but still few have linked it to business ethics, especially Islamic business ethics. This study aims to determine This study aims to determine the effect of organizational justice on employee engagement moderated by Islamic work ethics at Ratu Samban University (UNRAS), Bengkulu. The sampling technique used in this study is the census method, which is taking the entire population as a sample of the study. Based on the number of population then the sample in this study amounted to 80 respondents. The research variables consist of independent variables namely distributive justice, procedural justice and interactional justice, the dependent variable is the Employee Engagement, and the moderation variable is the work ethic of Islam. Data analysis in this study using hirearki regression analysis. The results of this study prove that Distributive Justice has a significant positive effect on Employee Engagement, Procedural Justice has a significant positive effect on Employee Engagement, Interactional Justice has a significant positive effect on Employee Engagement, Islamic Work Ethics moderate the effect of Distributive Justice on Employee Engagement, Islamic Work Ethics moderate the effect of Procedural Justice on Employee Engagement and Islamic Work Ethics moderate the influence of Interactional Justice on Employee Engagement.